Digitally enhanced community-based environmental monitoring: technologically upgrading the Enviro-Champs initiative - Pattinson, N. B.; Maharaj, U.; Singh, K.; Taylor, J.; Lepheana, A. T.; Dickens, Chris W. S.; Graham, P. M. (International Water Management Institute (IWMI). CGIAR Initiative on Digital Innovation, 2024)
Conventional water resource governance and monitoring systems, while essential, are falling short of requirements to address urgent challenges and achieve the Sustainable Development Goals (SDGs). Moreover, the global north and wealthy regions are typically overrepresented in science, while marginalised, disaffected and indigenous regions in developing countries, especially in the global south, remain underrepresented. Addressing these challenges requires diversified involvement that includes local community members who are disproportionately impacted by environmental and social problems.